Advanced intelligent computing theories and applications : with aspects of contemporary intelligent computing techniques, 4th International Conference on Intelligent Computing, ICIC 2008, Shanghai, China, September 15-18, 2008 : proceedings - International Conference on Intelligent Computing (4th : 2008 : Shanghai, China); Huang, De-Shuang (Berlin : Springer, 2008)
39